The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/eji.201242557
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dendritic cell differentiation of CD16‐positive monocytes in tuberculosis: Role of p38 MAPK

Abstract: Tuberculosis (TB) is one of the world's most pernicious diseases mainly due to immune evasion strategies displayed by its causative agent Mycobacterium tuberculosis (Mtb). Blood monocytes (Mos) represent an important source of DCs during chronic infections; consequently, the alteration of their differentiation constitutes an escape mechanism leading to mycobacterial persistence. We evaluated whether the CD16 + /CD16 − Mo ratio could be associated with the impaired Mo differentiation into DCs found in TB patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 59 publications
1
37
1
2
Order By: Relevance
“…For example, unlike our findings, some of previous studies have demonstrated that CD14 + CD16 + monocytes differentiate into CD1a -DCs exhibiting low immunostimulatory potencies, compared to CD1a + DCs differentiated from CD14 + CD16 -monocytes [18,19]. In addition, monocytes consisting of mostly CD14 + CD16 -cells could differentiate into CD1a -DCs upon exposure to inflammatory mediators such as microbial molecular patterns [34] and phospholipid metabolites including PGE2 [29,32].…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…For example, unlike our findings, some of previous studies have demonstrated that CD14 + CD16 + monocytes differentiate into CD1a -DCs exhibiting low immunostimulatory potencies, compared to CD1a + DCs differentiated from CD14 + CD16 -monocytes [18,19]. In addition, monocytes consisting of mostly CD14 + CD16 -cells could differentiate into CD1a -DCs upon exposure to inflammatory mediators such as microbial molecular patterns [34] and phospholipid metabolites including PGE2 [29,32].…”
contrasting
confidence: 82%
“…Monocytes consist of two populations, CD14 + CD16 -classical monocytes and CD14 + CD16 + non-classical monocytes [17], which differentiate into distinct DC subsets [18,19]. The proportion of CD14 + CD16 + monocytes is significantly increased in the blood of patients with systemic inflammatory diseases such as bacterial sepsis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Together, the modulation of these factors may be responsible for a bystander effect that allows M. tuberculosis to subvert the differentiation of monocytes into dendritic cells that are deficient in priming naïve T cells and, instead, contribute to pathogenic dissemination (Mariotti et al 2002;Skold and Behar 2008;Rajashree et al 2009). This premise is in line with the imbalance in the relative proportions of blood-circulating monocytes observed in tuberculosis patients, in which the abundance of the CD14 þ CD16 þ subset is accentuated and shown to have a defective differentiation program toward functional dendritic cells (Vanham et al 1996;Balboa et al 2013). In the case of IL-10, it was shown to be part of the bystander effect induced by M. tuberculosis to inhibit the differentiation of human monocytes into CD1c þ DCs, suggesting it plays an important role in the recruitment of dendritic cell precursors that may be incapable to activate efficiently the adaptive immune response (Remoli et al 2011).…”
Section: Dendritic Cell Differentiation and Activation: Manipulation supporting
confidence: 64%
“…This unbalance in the monocyte population is also associated with a higher cell-surface expression for CD14, CD11b, toll-like receptor-2 (TLR2), TLR5, chemokine C-C motif receptor-1 (CCR1), CCR2 and CCR5, as compared with that of healthy individuals [18]. Functional characterization in vitro shows that monocytes isolated from TB patients are refractory to efficient dendritic cell (DC) differentiation and deficient in the activation of T lymphocytes, as compared with monocytes from healthy donors [19,20]. The cause and consequence of this unbalance are still relatively unknown.…”
Section: Introductionmentioning
confidence: 99%